ANALISIS POTENSI KECELAKAAN KERJA PADA KEGIATAN PENAMBANGAN DAN PENGOLAHAN SERTA WORKSHOP DI PT. PULAU LEMON DISTRIK MANOKWARI SELATAN KABUPATEN MANOKWARI - Empi Iswandi; Indra Birawaputra (INTAN Jurnal Penelitian Tambang, 2019)
The importance of task identification using the job safety analysis method is to detail the works based on work sequences and risks possibly arisen. Job safety analysis can be used as a first step to find out the potential accident and to make accident controls. The results show that the potential accidents can be identified based on their severity. High risk, causing physical disability to death, occurs in gravel processing work using jaw crusher, gravel hauling, concrete mixing and casting. Moderate risk, causing treatments at hospital, includes welding, repairing excavator bucket, stacking and tidying material, screening stones and sand, and cutting iron. Low risk, that can be handled with first aids, includes excavating material, loading, painting iron frame, curling and straightening iron, repairing bulldozer body, repairing bulldozer machine, repairing dump truck glass, replacing dump truck coupling, replacing dump truck tires, replacing dump truck brake, repairing dump truck bucket, repairing excavator engine, repairing excavator crawler, and repairing engine of concrete pump trucks. In addition, PT. Pulau Lemon has not properly implemented the use of personal protective equipment and work protective equipment for their worker, therefore it is still needed to do some required improvement.